How can Blood Flow Restriction Exercise be Utilised for the Management of Persistent Pain Following Complex Injuries in Military Personnel? A Narrative Review - Luke Gray; Peter Ladlow; Russell J Coppack; Robyn P Cassidy; Lynn Kelly; Sarah Lewis; Nick Caplan; Robert Barker-Davies; Alexander N Bennett; Luke Hughes (Sports Medicine - Open)
Abstract Background Persistent pain is a complicated phenomenon associated with a wide array of complex pathologies and conditions (e.g., complex regional pain syndrome, non-freezing cold injury), leading to extensive disability and reduced physical function. Conventional resistance training is commonly contraindicated in load compromised and/or persistent pain populations, compromising rehabilitation progression and potentially leading to extensive pharmacological intervention, invasive procedures, and reduced occupational status. The management of persistent pain and utility of adjunct therapies has become a clinical and research priority within numerous healthcare settings, including defence medical services. Main Body Blood flow restriction (BFR) exercise has demonstrated beneficial morphological and physiological adaptions in load-compromised populations, as well as being able to elicit acute hypoalgesia. The aims of this narrative review are to: (1) explore the use of BFR exercise to elicit hypoalgesia; (2) briefly review the mechanisms of BFR-induced hypoalgesia; (3) discuss potential implications and applications of BFR during the rehabilitation of complex conditions where persistent pain is the primary limiting factor to progress, within defence rehabilitation healthcare settings. The review found BFR application is a feasible intervention across numerous load-compromised clinical populations (e.g., post-surgical, post-traumatic osteoarthritis), and there is mechanistic rationale for use in persistent pain pathologies. Utilisation may also be pleiotropic in nature by ameliorating pathological changes while also modulating pain response. Numerous application methods (e.g., with aerobic exercise, passive application, or resistance training) allow practitioners to cater for specific limitations (e.g., passive, or contralateral application with kinesiophobia) in clinical populations. Additionally, the low-mechanical load nature of BFR exercise may allow for high-frequency use within residential military rehabilitation, providing a platform for conventional resistance training thereafter. Conclusion Future research needs to examine the differences in pain modulation between persistent pain and pain-free populations with BFR application, supporting the investigation of mechanisms for BFR-induced hypoalgesia, the dose-response relationship between BFR-exercise and pain modulation, and the efficacy and effectiveness of BFR application in complex musculoskeletal and persistent pain populations.